2005
DOI: 10.1088/0264-9381/22/11/004
|View full text |Cite
|
Sign up to set email alerts
|

Isometric embeddings and noncommutative branes in homogeneous gravitational waves

Abstract: We characterize the worldvolume theories on symmetric D-branes in a six-dimensional Cahen-Wallach pp-wave supported by a constant Neveu-Schwarz three-form flux. We find a class of flat noncommutative euclidean D3-branes analogous to branes in a constant magnetic field, as well as curved noncommutative lorentzian D3-branes analogous to branes in an electric background. In the former case the noncommutative field theory on the branes is constructed from first principles, related to dynamics of fuzzy spheres in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 81 publications
(256 reference statements)
2
24
0
Order By: Relevance
“…For brevity we will only consider translation generators. Using the twist element (6.38) we arrive at the twisted coproducts [63] above to obtain the usual quantization of coadjoint orbits in nw(4) ∨ [62]. In exactly the same way that the noncommutative space Ê 3 ∞ of Section 6.1 above can be viewed as a collection of all fuzzy spheres, we can regard the noncommutative geometry of NW(4) as a foliation by all noncommutative S1-branes.…”
Section: Nappi-witten Plane Wavementioning
confidence: 99%
See 1 more Smart Citation
“…For brevity we will only consider translation generators. Using the twist element (6.38) we arrive at the twisted coproducts [63] above to obtain the usual quantization of coadjoint orbits in nw(4) ∨ [62]. In exactly the same way that the noncommutative space Ê 3 ∞ of Section 6.1 above can be viewed as a collection of all fuzzy spheres, we can regard the noncommutative geometry of NW(4) as a foliation by all noncommutative S1-branes.…”
Section: Nappi-witten Plane Wavementioning
confidence: 99%
“…Let us now introduce the one-formΛ := − i ϑ −1 x − 0 + ϑ x + z dz − z dz (6.34)on the null hypersurfaces of constant light-cone position x − = x − 0 , and compute the corresponding two-form gauge transformation of the B-field in (6.33) to getB −→ B + dΛ = − i ϑ dx + ∧ z dz − z dz + 2 i ϑ x − 0 dz ∧ dz . (6.35)Applying the Seiberg-Witten formula (5.3) to the closed string background fields (6.32) and (6.35) we compute[62]…”
mentioning
confidence: 99%
“…The background NW 6 arises as the Penrose-Güven limit [53,37] of an AdS 3 × S 3 background [11]. While this limit is a useful tool for understanding various aspects of string dy-namics, it is not in general suitable for describing the quantum geometry of embedded Dsubmanifolds [38]. In the following we will resort to a more direct quantization of the spacetime NW 6 and its D-submanifolds.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetric D-branes wrapping twisted conjugacy classes of the Lie group N were classified in [61]. Their quantization was analysed in [38] and it was found that, in the semi-classical regime, only the untwisted euclidean D3-branes support a noncommutative worldvolume geometry. We study these D3-branes as a special case of our more general constructions and find exact agreement with the predictions of the boundary conformal field theory analysis [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation